Growth Response of Juvenile Rohu (Labeo Rohita) to Wheatgrass Powder Supplemented Diet - Salam, Md Abdus; Rana, KM Shakil; Ahmmed, Md Rakib; Noor, Al Minan (Research in Agriculture Livestock and Fisheries, 2020)
Wheatgrass was evaluated as a potential non-conventional feedstuff to supplement fish meal in juvenile rohu (Labeorohita) diet to reduce feed cost. Green leafy sprouted wheatgrass (Triticumaestivum), inexpensive quality nutrient source, was processed into powder to formulate sinking pellet feed. Four isonitrogenous test diets were applied in four treatments (T) with three replications (R) each. The basal inclusion rate of fish meal was 30% in the control (T0), of which 10, 20 and 30% was replaced with wheatgrass powder in T10, T20 and T30 respectively to feed the experimental fish. Rohu fingerlings (7.63±0.41 cm; 4.66±0.15 g) were stocked in twelve glass aquaria (60×40×45 cm³) at 10 fish in 75 L water per aquarium, fed experimental diets at 5% of body weight twice daily. After 60 days of feeding trial, significantly better growth was observed in T20 with the highest production (3.23±0.44 tons/ha/60days), SGR (1.01±0.08 %/day) and the lowest FCR (2.68±1.40). Importantly, fish survival rate was improved with the progressive addition of wheatgrass in T10 (90%), T20 (93.33%) and T30 (100%) compared to the lowest survival in T0 (86.67%). Correspondingly fish in T30 were most resilient to low pH stress test (LT50 = 17 minutes) followed by T20 and T10 than T0 (LT50 = 9 minutes). Supplementation also resulted in better fish carcass quality with lowest carcass lipid (3.96±0.15%) and highest protein (15.72±0.53%) in T20 feed cost was reduced by 2.73, 5.13 and 8.06% in T10, T20 and T30 respectively than T0. Therefore, wheatgrass has prospect in juvenile rohu diet. Res. Agric., Livest. Fish.7(3): 533-543, December 2020